Synthesis and Spectroscopic of Some new Metal Ions Complexes's with [N-(4-Methoxy Benzoyl Amino)-Thioxo Methyl] Leucine - Sarhan, Basima M.; Hassan, Hassan A.; Fayyadh, Bushra M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new ligand [N-(4-methoxy benzoyl amino)-thioxo methyl ] leucine  (MBL) was prepared from the reaction of (4-methoxy benzoyl isothiocyanate with leucine acid in molar ratio (l:l), it was characterized by elemental analysis (C.H.N.S), FT-IR, UV-Vis, 1H and 13CNMR. The complexes of the bivalent ions (Mn, Fe, Co, Ni, Cu, Zn, Cd and Hg ) have been prepared and characterized too.       The structural was established by elemental analysis (C.H.N.S), FT-IR, UV-Vis spectra,  conductivity measurements atomic absorption and magnetic susceptibility and determination of molar ration (M:L). The complexes showed characteristic behavior of tetrahedral geometry around the metal ions except with (Cu) complex showed square planer.